Role of the cholinergic system in the psychopathology and treatment of schizophrenia: a protocol for a scoping review - Haczkiewicz, Michal; Hylén, Ulrika; Msghina, Mussie (Frontiers in Psychiatry, 2025)
Introduction and objectiveThe cholinergic system has broad implications for affective and cognitive processes, which makes it pertinent for the psychopathology and treatment of mental disorders. Questions concerning its role in schizophrenia, a chronic disorder characterized by psychosis, emotional blunting and cognitive deficits, have been made particularly relevant due to the recent Food and Drug Administration (FDA) approval of a muscarinic agonist as an antipsychotic agent. The present paper details the protocol for a scoping review that will map models, evidence and research gaps concerning the role of the cholinergic system in the positive, negative and cognitive domains implicated in the psychopathology of schizophrenia.Methods and analysisThe scoping review will be conducted according to JBI (formerly the Joanna Briggs institute) methodology, using articles from the following databases: PubMed, Embase, Scopus, Cochrane Central Register of Controlled Trials and PsycInfo. Two independent reviewers will screen the articles using title and abstract, after which full text-analysis will determine inclusion. Only published original peer-reviewed English-language studies from the last 20 years that pertain to the review objective will be included. Clinical studies will be assessed for methodological quality and risk of bias. The results, which the reviewers will extract independently of each other using a data extraction tool, will be presented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analysis Protocol Extension for Scoping Reviews (PRISMA-ScR).DiscussionClarifying the research gaps in the field can indicate where future pre-clinical and clinical studies and systematic reviews can be worthwhile, and the risk of bias assessment aids in this by stratifying the included clinical trials according to quality. However, the language and publication date restrictions risk excluding relevant studies, which can introduce bias.